(untitled) (Research, Society and Development, 2020)
The study evaluated the occurrence of violence against elderly people who are members of an Elderly Care Center and associated it with sociodemographic and functionality and health variables. For such, mixed and quali-quantitative methodologies or the triangulation of methods was used. From the quantitative research, the hope was to obtain the objective reality, while the necessary depth to understand the situations in which they experience violence, would be shown by the qualitative research. 66 elderly people were interviewed, with a mean and median age of 75 years, in which the main types of violence evidenced were: psychological, physical, financial and negligence, with the main gender of the victim being female. Among the factors related to the victims, the elders with mood disorder, as well as partially dependent are those who suffer the most violence. It was evidenced that all abuses addressed on the VASS scale (physical, psychological, financial and negligence) were present in the collected reports and were interconnected, demonstrating the simultaneity of different types of violence. The research also concluded that the lack of information and the underreporting of aggressions perpetuates violence, emphasizing the need for efficient public policies to protect the elderly.